Invisible herders? The archaeology of Khoekhoe pastoralists - Sadr, K. (Southern African Humanities, 2021)
Although based on strong historical, linguistic and ethnographic evidence, the conclusion that immigrant Khoekhoe pastoralists introduced the first livestock to southernmost Africa finds no convincing archaeological support. This may be for a number of reasons. Perhaps nomadic pastoralists leave no archaeological traces; or migrations are difficult to detect. Archaeology and the other disciplines may not be looking at the same thing. Or maybe the migrations date to the second millennium AD, long after the first livestock had reached southernmost Africa. It is not easy to tell: Later Stone Age animal bones, stones and pots do not broadcast the language and identity of the people who discarded them. To cite this article: Sadr, K. 2008. Invisible herders? The archaeology of Khoekhoe pastoralists. Southern African Humanities 20: 179-203.